Dengue Virus Utilizes a Novel Strategy for Translation Initiation When Cap-Dependent Translation Is Inhibited - Dianna Edgil; Charlotta Polacek; Eva Harris (2006)
ABSTRACT Viruses have developed numerous mechanisms to usurp the host cell translation apparatus. Dengue virus (DEN) and other flaviviruses, such as West Nile and yellow fever viruses, contain a 5′ m 7 GpppN-capped positive-sense RNA genome with a nonpolyadenylated 3′ untranslated region (UTR) that has been presumed to undergo translation in a cap-dependent manner. However, the means by which the DEN genome is translated effectively in the presence of capped, polyadenylated cellular mRNAs is unknown. This report demonstrates that DEN replication and translation are not affected under conditions that inhibit cap-dependent translation by targeting the cap-binding protein eukaryotic initiation factor 4E, a key regulator of cellular translation. We further show that under cellular conditions in which translation factors are limiting, DEN can alternate between canonical cap-dependent translation initiation and a noncanonical mechanism that appears not to require a functional m 7 G cap. This DEN noncanonical translation is not mediated by an internal ribosome entry site but requires the interaction of the DEN 5′ and 3′ UTRs for activity, suggesting a novel strategy for translation of animal viruses.